Development and Validation of a UHPLC-PDA-MS Method for the Quantitative Analysis of Anthraquinones in Bulbine natalensis Extracts and Dietary Supplements - Bae, Ji-Yeong; Avula, Bharathi; Wang, Yan-Hong; Wang, Mei; Ali, Zulfiqar; Viljeon, Alvaro M.; Khan, Ikhlas A. (Planta Medica, 2020)
A UHPLC-photodiode array-MS method was developed and validated for the quantification of one chromone and six anthraquinone type of compounds from Bulbine natalensis plant samples and dietary supplements. Metabolites 1 – 7 were identified based on their retention times and electrospray ionization-MS spectra compared with a mix of previously isolated compounds. The quantification of 1 – 7 was based on photodiode array detection. The optimized separation was achieved using a CORTECS C18 column with a gradient of water/acetonitrile as the mobile phase. Seven compounds were separated within 15 minutes with detection limits of 50 pg on the column. The analytical method was validated for linearity, repeatability, accuracy, limits of detection, and limits of quantification. The relative standard deviations for intra- and inter-day experiments were less than 5% and the recovery efficiency was 98 – 101%. Nine dietary supplements labeled as containing B. natalensis were examined. Anthraquinone-type compounds were detected in only five out of nine dietary supplements, with the total amount ranging from 11.3 to 90.4 mg per daily dose. The analytical method is simple, economic, rapid, and can be applied for quality assessment of B. natalensis and dietary supplements. Electrospray ionization-MS was used for the identification of these compounds in plant samples and dietary products.
Keywords: Bulbine natalensis; Asphodelaceae; anthraquinones; dietary supplements; UHPLC-PDA-MS